Juridical Review of Land Grants in Pandan Sub-District, Central Tapanuli Regency, in the Perspective of Law no.5 of 1960 on Basic Agrarian Principles - Patricia, Andi Yohani; Lubis, Syofiaty (LEGAL BRIEF, 2024)
This study aims to conduct a juridical review of land grants based on Law No. 5 of 1966 TPA in the Pandan Subdistrict, Tapanuli Tengah Regency. The research method used is normative legal research with legislative, historical, and conceptual approaches. This study summarizes the findings of previous relevant studies, establishes the theoretical or conceptual framework used as a basis for analysis, discusses the findings and analysis that emerge from this study, and formulates the main conclusions along with relevant implications. The results of the study indicate that a deep understanding of the legal regulations governing land grants is crucial, and active involvement from all relevant parties is also required. Furthermore, a balanced consideration of moral aspects and legal values must also be observed in the land grant process. The implication of this study is the need for an enhanced legal understanding among all parties involved in land grant transactions and collaborative efforts to ensure the effective implementation of existing legal regulations